Pendapatan keluarga dan penyediaan pangan sehat dan bergizi pada rumah tangga di Desa Cot Darat Kecamatan Samatiga Kabupaten Aceh Barat - Rahayu Utami; Nazliana Nazliana (Journal of Health and Therapy, 2023)
Providing healthy and nutritious food is an important factor in supporting family food security and the nutritional status of household members. In Cot Darat Village, Samatiga District, West Aceh Regency, limited family income is suspected to affect households' ability to meet diverse and nutritious food needs. This study aims to describe family income and patterns of providing healthy and nutritious food in households with toddlers. The study used a descriptive design with a survey approach. The study population consisted of 70 fathers of toddlers, with a sample of 41 respondents selected using a purposive sampling technique. Family income data were collected using a questionnaire and analyzed univariately. The results showed that 78.04% of families had incomes below Rp3,165,000. Family food expenditures consisted of side dishes (38%), staple foods (20%), fruits (15%), spices (14%), and vegetables (13%). Most families still have low incomes, which potentially impacts the provision of healthy and nutritious food. The results of this study can be a basis for the government and community in improving efforts to empower families' economies and fulfill household nutritional needs.